La sociolingüística de la variació als Països Catalans: estat de la qüestió - Mas i Miralles, Antoni; Montoya i Abad, Brauli (Caplletra. Revista Internacional de Filologia, 2004)
The results of an analysis on literature about microsociolinguistics, where you can also see a lack of theoretical congruence, are shown in this paper. The authors classify the works in three groups, depending on the community with which they deal: communities where the main spoken language is Catalan, communities where it is Spanish or communities where Catalan became extinct. From the first two groups, they review phonological and morphological studies. From the third, they suggest the study of language vestiges in communities where Catalan became extinct. Finally, they claim that macro and microsocionlinguistics should be unified and remark the interest of language variation studies for the language planning.